Prevalence and determinants of iron deficiency in cardiac amyloidosis. (6th February 2022) - Jobbé‐Duval, Antoine; Bézard, Mélanie; Moutereau, Stéphane; Kharoubi, Mounira; Oghina, Silvia; Zaroui, Amira; Galat, Arnault; Chalard, Coraline; Hugon‐Vallet, Elisabeth; Lemonnier, Francois; Eyharts, Damien; Poulot, Elsa; et al.
Abstract: Aims: Iron deficiency (ID) is common in patient with chronic heart failure (HF) and has been widely studied. In contrast, data concerning ID in cardiac amyloidosis (CA) are limited. Amyloidosis is a severe and fatal systemic disease, characterized by an accumulation of amyloid fibrils in various tissues/organs, including nerves, kidneys, gastrointestinal tract, and heart. Amyloid deposits in the heart eventually cause HF. The main subtypes of CA are light chain (AL), hereditary transthyretin (ATTRv), and wild‐type transthyretin (ATTRwt). We performed this study to determine the prevalence, clinical outcome (all‐cause mortality), and determinants of ID among the three main subtypes of CA. Methods and results: Iron deficiency status were analysed in 816 CA patients enrolled at the French Referral Centre for Cardiac Amyloidosis: 271 (33%) had AL, 164 (20%) ATTRv, and 381 (47%) ATTRwt. ID affected 49% of CA patients, 45% with AL, 58% with ATTRv, and 48% with ATTRwt. We identified ATTR status (ATTRv P = 0.003, ATTRwt P = 0.037), diabetes ( P = 0.003), aspirin treatment ( P = 0.009), haemoglobin levels ( P = 0.006), and altered global longitudinal strain ( P = 0.02) as independent ID determinants. There is no difference in all‐cause mortality considering ID status. Conclusions: Iron deficiency is common in patients with CA, irrespective of the subtype. Patients seem more likely to have ID if diagnosed with ATTR, if diabetic, and/or treated with aspirin. In CA, the benefit of intravenous iron therapy, for ID, on morbidity and mortality needs further study.